Contrastive Analysis of Vocal Phoneme Changes in the Affixation Process in Japanese and Indonesian: morphophonemic studies - Rama Ulun Sundasewu (Universitas Diponegoro, 2023)
This research conducted by analyzing similarities and differences of phoneme changes on Japanese and Indonesian affixation process. The purpose of this research is to find out the similarities and differences of vowel phoneme changes on Japanese and Indonesian affixation process. This research is qualitative research, using the contrastive analysis with descriptive metods. Object of research is vowel phoneme that change on Japanese and Indonesian affixation process. Result of this study indicates that the similarities of the vowel changes on affixation are the Japanese /me/ prefix and Indonesian /me-/ prefix that do not have changes, but having the addition of phoneme when vowel phoneme follows. And the differences of vowel on affixation are Japanese /me/ and /o/ prefixes have the addition of phoneme, but Indonesian /me-/ and /ber-/ prefixes do not have. <a href=